Green computing: The importance of sustaining the peopleware - Noordin, Mohamad Fauzan (IGI Global, 2015)
Green Computing has attracted concerns in the past few decades, with the sole concern for the procedures involve in the designing, manufacturing, usage and disposal of information and communication technology (ICT) basically for environmental sustainability. The importance of human factor in green computing has not received the deserved attention. The social, moral and ethical decadence resulting from the use of ICT has reduced the quality of human in modern time. This study advocates the importance of peopleware as essential aspect of green computing which equalling demands concern. Thus the adoption of peopleware in green computing practices will invariably improve sustainability of the physical and spiritual environment.